The Climate Change Related Adaptation and Resilience of Traditional Tradicional Dwellings: the Case of Yucatan Penisula - Joel Audefroy; Bertha Nelly Cabrera Sanchez (Ochrona Dziedzictwa Kulturowego, 2021)
Mexico has been affected by extreme events such as storms, hurricanes, floods, and wildfires in the past ten years. In this paper, we will attempt to respond to the following questions: What are the climate change effects on the architectural heritage of Maya housing, and what are the adaptation and resilience practices of Maya housing and its environment?